(untitled) (International Journal of Applied Research in Management and Economics, 2018)
It is estimated that globally over 2.5 billion people are excluded from access to financial services of which one third is in India. Though the reach and scope of banking have thus increased, the huge demand for financial services remains insatiate. It is a matter of concern that even with 150 domestic commercial banks comprising 19 Public Sector Banks, 20 Private Sector Banks, 44 Foreign Banks, 4 Local Area Banks, 56 Regional Rural Banks and over 2,700 Co-operative Banks operating in the country, just about 40 percent of the adults have formal bank accounts1.To widen the scope of the banking sector reforms, the Centre focused on financial inclusion, digital banking, and better risk management. Various initiatives have been taken by the Reserve Bank of India for strengthening financial inclusion. One such initiative is the issue of Differentiated Banking Licenses to financial institutions to convert themselves into either Payment Banks or Small Finance Banks.RBI issued in-principle approval to start 11 Payment Banks and 10 Small Finance Banks. Financial inclusion plays a major role in the inclusive growth of the country. The growth of our economy is dependent on the growth of rural India. The availability of quality financial services in rural areas will enable a large number of rural households to fund the growth of their livelihoods. The present paper focuses on the study of Small Finance Banks and their role in promoting financial inclusion in India.